Etnomatematika: Eksplorasi Konsep Matematika Pada Gapura Masjid Jamik Sumenep - Alghar, Muhammad Zia (Department of Mathematics Education, Faculty of Tarbiyah, Institut Agama Islam Negeri Parepare, 2024)
One of the goals of National Education is to create cultured human beings and appreciate the diversity of national culture. The approach to mathematics through cultural aspects is offered in ethnomathematics. This ethnomathematics research aims to reveal the mathematical concepts and cultural values inherent in the gate of the Sumenep Jamik Mosque. A qualitative method with an ethnography type was used in this research. Research data were collected through observation, interviews, documentation, and literature studies. The results showed the existence of mathematical concepts in the ornament of the Mosque Jamik Sumenep in fractal geometry, the idea of reflection on the transformation of geometry, ratio, and angle. Also, cultural values include the meaning of the swastika symbol, the T key motif, and the value of cultural acculturation. The findings of this study can be developed in learning tools and become a reference to be applied in ethnomathematics-based learning in the classroom.